The Responsiveness and the Ability of “Kampung Tangguh Bencana” in Handling Flood in Yogyakarta City - Ambar Teguh Sulistiyani; Kristi Yuliani; Muammar Yuliana (Department of Urban and Regional Planning, Universitas Diponegoro, 2017)
Yogyakarta City is passed by three rivers, i.e. Winongo River, Code River, and Gajahwong River. Due to that geological condition, Yogyakarta City is prone to annual flood more often than the other types of disaster. Dealing with the risk, the Yogyakarta City Government introduces Kampung Tangguh Bencana or disaster resilient villages (DRV). DRV is a village which has an ability to identify hazards in its environment and is able to organize the human resources in reducing the susceptibility as well as increasing the capacity to reduce the disaster risks. These abilities are carried out in development planning and capacity enhancement in restoration after the emergency condition. Thus, it is important for DRVs to understand the responsiveness and the ability to become autonomous in flood counter-measurement in Yogyakarta City. In order to find out the responsiveness of DRVs in handling the flood, a research using qualitative approach was performed through a set of interviews with key persons. Information was gained from related stakeholders, such as the local government officers, community, and local agency for disaster management (Badan Penanggulangan Bencana Daerah or BPBD) as the organizer of the program. Triangulation method was performed to find out the synchronization between stakeholders. The villages observed in this research were Karanganyar, Warungboto, and Wirobrajan which were located on the river bank. The result of this research covered the description in handling flood through DRVs, the form and identity of DRVs, the contract-expand model action in the management phases of disaster, as well as the advantages and weaknesses of DRVs. The data gained was analyzed in depth by comparing the responsiveness and the ability to become autonomous in the three villages. The recommended formulation was given to the DRVs, the local government, and the local community to carry out the DRVs effectively and sustainably.